The Relationship Between Teachers’ Competence and Their Job Satisfaction at Phaung Daw Oo Monastic Education High School, in Mandalay Division, Myanmar - Ar Tha Bha, U.; Ye, Yan (Scholar: Human Sciences, 2020)
The main purpose of this study was to identify the level of teachers’ competence and job satisfaction at Phaung Daw Oo Monastic Education High School, in Mandalay Division, Myanmar; and also to determine whether there is significant relationship between teachers’ competence and teachers’ job satisfaction at Phaung Daw Oo Monastic Education High School, in Mandalay Division, Myanmar. A total of (150) full– time teachers from the Phaung Daw Oo Monastic Education High School, in Mandalay Division, Myanmar during the academic year of 2017 – 2018 were surveyed for this study. The design of this research was a quantitative and correlation study based on Medley (1977) teachers’ competence and Herzberg two factors motivation theory (1959) job satisfaction. The questionnaires used for this study consisted of two parts. In part one; the researcher used the questionnaire adopted from Huyen (2003) to identify the level of teachers’ competence. It contained (33) items for five dimensions. In part two, the researcher used the questionnaire adopted from King Sothina (2014) which was developed and originally used by Lester (1984) to identify the level of teachers’ job satisfaction. It contained (27) items for four dimensions. The collected data were analyzed by using the mean, standard deviation to identify the level of teachers’ competence and job satisfaction and Pearson Product Moment Correlation Coefficient to determine whether there is significant relationship between teachers’ competence and teachers’ job satisfaction at Phaung Daw Oo Monastic Education High School, in Mandalay Division, Myanmar. This research found that the level of teachers’ competence and job satisfaction was at a high level; and there was a significant relationship between teachers’ competence and teachers’ job satisfaction at Phaung Daw Oo Monastic Education High School, in Mandalay Division, Myanmar.